Violence and peer aggression – contexts and prevention - Ruszaj, Zbigniew (Edukacja • Terapia • Opieka, 2020)
The functions of the educational institutions include providing care, safety, educational and preventive activities for children. For the proper realisation of those tasks essential are accurate diagnosis/study of the school environment in this peculiar area/sphere and precise prearranging of specific actions against particular threats and among the particular groups of children. In the process of preventive planning the important role plays recognition of children’s developmental differences, forms of aggression, and individual needs of particular class teams.